PENGEMBANGAN PENDEKATAN PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES BAGI MAHASISWA S1 PGMI IAIN SNJ CIREBON - Atikah Syamsi (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2015)
To  support efficacy of study,  basically to determine  approach of  study  which in line with curriculum. Studying approach of study, a lot of type approach of  which  can  applied.Among others  approach  of  developed  study from an recognized  theory with  theory  of Multiple  Intelligence.The  Theory used  as  by approach of  study,  because it talk about variety  which  related  to  educative participant  interest.Basically in each of curriculum is  focus  to  attainment  an certain  interest to  educative participant. Approach of Multiple Intelligence even also look into that human being or someone have some intellegence potency. One of the intellegence educative by participant  that's which must be developed, so that in the end become an its very dominant interest.One of the matter which need to be paid attention in Multiple Intelligence is the existence of education institutes responsibility to be succeeding  to find  at least one ability region matching with  its intellegence  potency and this matter have positive  implication to make-up of  its  life or which is ordinary to be recognized with term of  make-up  of life skills.Quality  of Indonesia  human resource these days is reflection of education system which in this time  go into effect.This research represent Research and Development (having the character of research applied) that is research used to look for, to developing and testing an certain finding or  product. This Research type is reseacrh of  Experiment with approach of mixture that is qualitative and is quantitative, where this research aim to develop new approach that is  intelligences multiple to  student of PGMI IAIN SNJ  Cirebon. This Matter because of  the  importance of  education  which peculiarly refer  at student  skill soft  as behavioral base of  academic, namely  for example mirror of education base on intelligences multiple which practically can improve  efficiency  of someone  life and  it is  of  course  also  be  benefit to  its environment. By having efficiency ofÂ  life which is good to be,  expected  by all college grad will be able to solve life problema faced.